High‐yield production of a human monoclonal IgG by rhizosecretion in hydroponic tobacco cultures. Issue 2 (3rd June 2015) - Madeira, Luisa M.; Szeto, Tim H.; Henquet, Maurice; Raven, Nicole; Runions, John; Huddleston, Jon; Garrard, Ian; Drake, Pascal M.W.; Ma, Julian K‐C.
Summary: Rhizosecretion of recombinant pharmaceuticals from in vitro hydroponic transgenic plant cultures is a simple, low cost, reproducible and controllable production method. Here, we demonstrate the application and adaptation of this manufacturing platform to a human antivitronectin IgG1 monoclonal antibody (mAb) called M12. The rationale for specific growth medium additives was established by phenotypic analysis of root structure and by LC‐ESI‐MS/MS profiling of the total protein content profile of the hydroponic medium. Through a combination of optimization approaches, mAb yields in hydroponic medium reached 46 μg/mL in 1 week, the highest figure reported for a recombinant mAb in a plant secretion‐based system to date. The rhizosecretome was determined to contain 104 proteins, with the mAb heavy and light chains the most abundant. This enabled evaluation of a simple, scalable extraction and purification protocol and demonstration that only minimal processing was necessary prior to protein A affinity chromatography. MALDI‐TOF MS revealed that purified mAb contained predominantly complex‐type plant N ‐glycans, in three major glycoforms. The binding of M12 purified from hydroponic medium to vitronectin was comparable to its Chinese hamster ovary (CHO)‐derived counterpart. This study demonstrates that in vitro hydroponic cultivation coupled with recombinant protein rhizosecretion can be a practical, low‐cost production platform for monoclonal antibodies.